Gérer les migrations, gérer les migrants: une perspective historique et transnationale sur les migrations dans les monarchies du Golfe - Hélène Thiollet (Arabian Humanities)
This paper looks at migration management in the Gulf monarchies since the 1930s. It describes the dynamics of labour import and immigration policies, and highlights the hybrid and transnational nature of migration management. Indeed, migration flows and migrants’ lives are structured by both public and private actors and institutions, operating between home and host countries. Transnationalism in this article is taken to mean the transnational politics of migration management, as opposed to the usual understanding of migrant transnationalism. Thus, this paper describes the political strategies of States at the national and international (or diplomatic) level. It also examines private actors in general and the oil companies in particular, as they have helped shape both migration flows and migrant lives in the Gulf monarchies during the 20th century. Based on this description, our aim is to conceptualize migration management as an illiberal form of transnationalism.